The impact of pelletized biochar soil application on sweetcorn growth and productivity - Sulaiman, Muhammad Firdaus; Abdullah Zawawi, Ahmad Nazri; Mahmud, Khairil; Mohd Amin, Adibah; Adrian, Marie M.; Mohd Ali, Miratul Hada (Malaysian Society of Soil Science, 2024)
Biochar application to soil improves soil health, recycles biomass waste, and sequesters carbon. However, biochar's small size and dusty character make it a health hazard when applied. Pelletized biochar has the potential to overcome this issue but, its reduced surface area may affect its effectiveness as a soil amendment. The present study compared the impacts of applying pelletized biochar with unpelletized biochar on the physical and physiological characteristics of sweetcorn, as well as the chemical properties of the soil. The study consisted of five treatments arranged in a randomized complete block design (RCBD): i) unpelletized bamboo biochar (UBB), ii) pelletized bamboo biochar (PBB), iii) pelletized rice husk biochar (PRHB), iv) unpelletized rice husk biochar (URHB), and v) a control group with no biochar application. The application rate for all biochar treatments was 6 Mg ha -1. The study found that the pelletized biochar did not significantly differ from unpelletized biochar for both bamboo and rice husk in terms of soil physical and chemical characteristics. There were no significant differences in plant height, plant leaf area, total leaf area, photosynthetic rate, final biomass, and corn yield between pelletized biochar and unpelletized biochar treatments. The present study demonstrated that compressing biochar into pellets did not render its quality inferior to unpelletized biochar, thus potentially solving its health hazard issue without compromising its efficacy, potentially increasing the widespread use of biochar as a soil conditioner.